What a hard way of doing it.
look at the second equation, it is very easy to solve for x
x = 8+y
now sub that into the first
3(8+y) - y = 8
24 + 3y - y = 8
2y = -16
y = -8
back in x = 8+y
x = 8+(-8) = 0
Your last two lines of step1 are wrong
should have been
3x/3=(8+y)/3
x=(8+y)/3
of course that makes all the statements is Step 2 incorrect.
I am solving for linear equations and I'm wondering if I did Step 3 right..
3x-y=8
x-y=8
Step 1
3x-y=8
3x-y+y=8+y
3x=8+y
3x/3=8+y/3
x=(8+y/3)
Step 2
3(8+y/3)-y=8
8+y-y=8
8+2y=8
8+2y-8=8-8
2y=0
2y/2=0/2
y=0
Step 3
x=8+y(0)/3
x=2.6
1 answer